2002
DOI: 10.1023/a:1014849028575
|View full text |Cite
|
Sign up to set email alerts
|

A Convergent Variant of the Nelder–Mead Algorithm

Abstract: Abstract. The Nelder-Mead algorithm (1965) for unconstrained optimization has been used extensively to solve parameter estimation (and other) problems. Despite its age it is still the method of choice for many practitioners in the fields of statistics, engineering, and the physical and medical sciences because it is easy to code and very easy to use. It belongs to a class of methods which do not require derivatives and which are often claimed to be robust for problems with discontinuities or where the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 10 publications
0
94
0
Order By: Relevance
“…This is in the spirit of several of the early direct search methods such as Rosenbrock's method of rotating directions [227], Powell's method based on conjugate directions [213], and the adaptive simplex of Nelder and Mead [194]. The algorithmic strategies in the former two papers, in particular, informed the developments in [76,77,224].…”
Section: And αmentioning
confidence: 97%
“…This is in the spirit of several of the early direct search methods such as Rosenbrock's method of rotating directions [227], Powell's method based on conjugate directions [213], and the adaptive simplex of Nelder and Mead [194]. The algorithmic strategies in the former two papers, in particular, informed the developments in [76,77,224].…”
Section: And αmentioning
confidence: 97%
“…Due to the difference in the acquisition frequency between the camera and the measurement arm, the pose assigned to an image was interpolated from the two nearest neighbors using linear interpolation for the translational part and spherical interpolation for the rotational part. We used the NelderMead algorithm [15] to jointly optimize t o f f set and T ext for each sequence, starting with t o f f set = 0 and with the result of the manual registration for T ext .…”
Section: Post-processing the Dataset Acquisitionmentioning
confidence: 99%
“…Also, it has recently been shown that in some cases the N M method will not converge, as in McKinnon [7]. More complicated variants have been developed (see for example Price et al [11]) that guarantee convergence. However, none of these difficulties occurred here, and the standard NM method was acceptable.…”
Section: The Nelder-mead Downhill Simplex Methodsmentioning
confidence: 99%
“…https://doi.org/10.1017/S1446181100013456 [11] Maximising output from oil reservoirs without water breakthrough …”
Section: Non-negative Nelder-mead On the Feasible Boundarymentioning
confidence: 99%